Anti-Aging Potential and Quercetin Determination of Melastoma malabathricum L. Leaves Extract - Amalia, Thia (Pharmaceutical Journal of Indonesia, 2024)
Background: Melastoma malabathricum L. is a wild shrub that traditionally used in South-East Asia as wound healing. Plant extracts contain phenolic, flavonoid and tannin. The leaves extract also has many pharmacological activity but the anti-aging activity of the leaves extract has not been studied. Methods: The leaves of M. malabathricum was defatted with chloroform and then refluxed by ethanol. Quercetin content of the leaves extract was determined by HPLC. Anti-aging activity was evaluated by anti-elastase, and anti collagenase inhibitor activity of the leaves extract by a fluorometric method. Results: Percentage yield of the M. malabathricum leaves extract was 16.53% w/w. Quercetin content of the leaves extract was 9.20 mg/g extract. The leaves extract of M. malabathricum L. has anti-elastase and anti collagenase activity with IC50 80.39±2.36 ppm and 63.3±3.32 ppm, respectively. Conclusions: M. Malabathricum leaves extract was potential as an anti-aging cosmetic raw material.